Comparison of the results of minimal invasive repair of pectus excavatum between patients aged at and over 40 years with under 40 years of age - YÜKSEL, MUSTAFA (My University, 2023)
Introduction: Minimal invasive repair of pectus excavatum (MIRPE) which is used in the treatment of pectus excavatum is recommended for patients aged 12–16 years, over 30 years of age are called an advanced age. In this study, we aimed to evaluate the outcomes of patients in aged at and over 40 years. Patients and Methods: It is a single-center, retrospective study. Those aged 39 and under were grouped as group 1 (n = 10), and those aged 40 and over as group 2 (n = 10). We compared the results between in the two groups. Results: Of 80% were male with a mean age of 40.4 ± 16.03 years. A between-group comparison of the parameters are the Postoperative Haller index (p < 0.00), Physician Evaluation Score (p < 0.00), and presence of a drain (p < 0.03) to be statistically significantly different. Spearman rank correlation analysis was performed to determine the correlation between age and variables found to be statistically different between the two groups. There is positively and moderate correlation between patient’s age and their hospital stay (r = 0.540, p < 0.05), positive and high-level correlation between age and the Postop Haller index (r = 0.727, p < 0.01). There is negatively and moderate correlation (r = − 0.447, p < 0.05) between patients’ age and patient evaluation score, negative, and high-level between age and doctor’s evaluation score (r = − 0.772, p < 0, 01). Conclusion: This study demonstrated that MIRPE can confer equal benefit and may be offered surgical correction of PE by the MIRPE technique in those of older ages.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery; MIRPE; Older age; Pectus excavatum